Pengaruh Manajemen Laba terhadap Peringkat Obligasi pada Saat Emisi - Tri Wahyudi; Bambang Sugeng Dwiyanto (Jurnal Maksipreneur, 2014)
This study was conducted to prove empirically the earnings management practices related to its influence on the bond rating. The data of this study were 36 companies that issued bonds listed on Valuation, published in 2010-2012. Sampling method using purposive sampling method. Detection of earnings management behavior in this study using the Modified Jones Model (1995). Data were analyzed using classical assumption, namely: autocorrelation, heteroscedasticity test, and test for normality. Hypothesistesting using multiple regression analysis with SPSS16.